Primary Non-Hodgkin’s Lymphoma of the Female Urethra Presenting as Carunculous of Urethra: A Very Rare Case Report - Tan Hengky; Nanda Daniswara; Ardy Santosa; Adi Soedarso; Eriawan Agung Nugroho; Sofyan Rais Addin (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background: Female urethral carcinoma occurred < 1% of all female malignancies. With a small prevalence of Malignant Urethral Lymphoma, there is lack of data about quality of the therapy. Case Report: A 41-year-old woman came to Division of Urology, Department of Surgery Dr. Kariadi Hospital Semarang with chief complaint a recurrence mass on her urethra. Her general condition was fine, and has a normal vital signs. On the physical examination of urogenital region, there was mass on the orifice of urethra external that can easily bleed. She is already performed excision of urethral caruncle with immunohistochemistry examination and found CD-20 positive which indicated a diffuse B-cell Lymphoma. Then she had 6 cycle chemotherapy procedures in Division of Hematooncology, Internal Medicine Department. Until now, she routinely check-up to urology and internal medicine departments to monitor her disease progression. Conclusion: Female urethral carcinoma is very rare, although surgery alone has been established as effective for treating low-stage urethral cancer, neither surgery nor radiation therapy alone provide good results. Delay in diagnose and treatment can decrease patient survival. Keyword: non-Hodgkin’s lymphoma, immunohistochemistry, Urethral carcinoma, urethral caruncle, chemotherapy